The effects of university students’ co-curicular activities on academic performance: A case study in UiTM Kelantan, Kampus Kota Bharu / Mohd Faris Mohd Fauzan - Mohd Fauzan, Mohd Faris (2014)
Co-curricular activities previously known as extracurricular activities are activities that educational organizations in some parts of the world create for university students. They are activities which all university students must attend alongside. This study focuses finding a multiple linear regression model based on the factors that affect student academic performance. These factors are multiple positions, experience, attendance performance and time management which are related to the student when they are participating co-curricular activities. This study provides better explanation to the university students where participating in co-curricular activities either gave them good advantage or disadvantage. Furthermore, this study also can be used by the university in order to give better understanding about the factors that affect student academic performance while taking part in co-curricular activities. However, the study was limited by the validity of the results students received in their academic, thus affecting the grade point average (GPA) to the university. At the end of this study, it was found that the factors (multiple position, experience, attendance performance, and time management) contributed significantly to the student academic performance